2019
DOI: 10.1155/2019/6515797
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation on the Correlation between the Mechanical Properties of Human Skull Bone, Its Geometry, Microarchitectural Properties, and Water Content

Abstract: With increasingly detailed imaging and mechanical analysis, modalities need arises to update methodology and assessment criteria for skull bone analysis to understand how bone microarchitecture and the presence of attached tissues may affect the response to mechanical load. The main aim was to analyze the effect of macroscopic and microstructural features, as well as periosteal attachment, on the mechanical properties of human skull bone. Fifty-six skull specimens from ethanol-phenoxyethanol-embalmed cadavers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 29 publications
1
29
0
Order By: Relevance
“…Maybe this trend is specific to fibula which is not a weight-bearing bone and could explain that the mechanical environment (external forces) is less determinant in the evolution of this bone with aging especially in the microstructure orientation so the correlation between microstructural parameters and mesoscopic stiffness coefficients is lost with age. This assumption is in accordance with a recent study on the skull 30 . Several papers demonstrate that in femur or tibia for example which are bearing bones, mesoscopic mechanics are highly correlated to microstructure even for adult cortical bone 31 34 .…”
Section: Discussionsupporting
confidence: 93%
“…Maybe this trend is specific to fibula which is not a weight-bearing bone and could explain that the mechanical environment (external forces) is less determinant in the evolution of this bone with aging especially in the microstructure orientation so the correlation between microstructural parameters and mesoscopic stiffness coefficients is lost with age. This assumption is in accordance with a recent study on the skull 30 . Several papers demonstrate that in femur or tibia for example which are bearing bones, mesoscopic mechanics are highly correlated to microstructure even for adult cortical bone 31 34 .…”
Section: Discussionsupporting
confidence: 93%
“…The here reported B strength of 67 MPa is similar to the values of 85 MPa obtained from frontal and parietal regions of eight fresh-frozen cadavers using a testing velocity of 30,000 mm/min 12 and the 64 to 86 MPa obtained from 114 unembalmed fronto-parietal samples using a testing speed of 0.06 mm/ min 10 . A study involving Crosado-embalmed 42 cadavers using an identical testing velocity as in the given study of 10 mm/min reported a lower B strength of 42 MPa and 53 MPa for the two investigated human neurocrania 6 , likely due to an embrittlement of the tissue following the chemical treatment or a statistical bias caused by the low sample size in the former work. The B strength of the composite group in this given study decreased with age, presumably caused by the concomitant age-related thickening of the samples without a concurrent increase of F max values.…”
mentioning
confidence: 65%
“…In contemporary finite element models, the diploë is either neglected or represented in an oversimplified manner due to the lacking or controversial material properties that are available in the scientific literature 5 . Previous research regarding the load-deformation behavior of the human neurocranium mainly focused on full-thickness composites 6 17 . Only few studies investigated the two tables 7 , 18 – 23 or even the cancellous diploë layer individually 13 , 18 , 24 , 25 .…”
Section: Introductionmentioning
confidence: 99%
“…Probably, not only the sutures allow the transmission of forces deriving from the movement of the nervous system but also the structure of the skull bone itself. The bones that make up the skull have elastic properties, with the temporal bone having the maximum ability to withstand tension, down to the least compliant bone such as the frontal bone [19]. Furthermore, the underlying dura mater and the periosteum, which is a continuum with the underlying tissue through the Sharpey's perforating fibers, collaborate for the most correct management of mechanical signals [19].…”
Section: Review Joint Mobility Of the Skull Bonesmentioning
confidence: 99%
“…The bones that make up the skull have elastic properties, with the temporal bone having the maximum ability to withstand tension, down to the least compliant bone such as the frontal bone [19]. Furthermore, the underlying dura mater and the periosteum, which is a continuum with the underlying tissue through the Sharpey's perforating fibers, collaborate for the most correct management of mechanical signals [19]. The bone tissue contains elastin and collagen and together they ensure a capacity of mechanical deformation of about 10%-15%.…”
Section: Review Joint Mobility Of the Skull Bonesmentioning
confidence: 99%